THE INTEGRATION BETWEEN CORPORATE AND OPERATIONAL STRATEGIES: AN ANALYSIS OF SCIENTIFIC PUBLICATIONS USING A BIBLIOMETRIC METHOD - Treinta, Fernanda; Filho, José Rodrigues de Farias; Chagas, Daniela Lopes; de Oliveira, Lucas Rebello; Rocha, Michele Medeiros; Medeiros, Raffaela Martins; Mansur, Rodrigo Teofilo (Brazilian Journal of Operations & Production Management, 2014)
When a research about the integration between corporate and operational strategies is performed, an exhaustive number of scientific publications arise. To filter and selecting the more relevant papers for the Production Engineering field becomes a difficult task. Therefore, the Bibliometric method was chosen in order to select and evaluate the publications around the theme. Starting from a keyword tree, 1174 papers were analyzed by the software Refviz® and 276 papers were selected. Using 18 indicators, conclusions about the main authors, economic sectors, vehicle of publication, institutions and countries that have published could be inferred, allowing a consistent evaluation of this important theme.